Genome-wide identification of the GATA gene family in melon (Cucumis melo) and analysis of their expression characteristics under biotic and abiotic stresses - Zheng, Ling; Tang, Lin; Li, Jinbo (Frontiers in Plant Science, 2024)
GATA transcription factors are an important class of transcription factors in plants, known for their roles in tissue development, signal transduction, and responses to biotic and abiotic stresses. 24 CmGATA genes were identified from the melon genome. These family members exhibit significant differences in protein length, molecular weight, and theoretical isoelectric point, and are primarily located in the nucleus. Based on the classification of Arabidopsis thaliana GATA members, the phylogenetic tree divided them into four groups: Group I, Group II, Group III, and Group IV, containing 10, 8, 4, and 2 genes, respectively. Notably, CmGATA genes within the same group have highly conserved protein motifs and similar exon-intron structures. The CmGATA family members are unevenly distributed across ten chromosomes, with six pairs of segmentally duplicated genes and one pair of tandemly duplicated genes, suggesting that gene duplication may be the primary factor in the expansion of the CmGATA family. Melon shares 21, 4, 38, and 34 pairs of homologous genes with A. thaliana, Oryza sativa, Cucumis sativus, and Citrullus lanatus, respectively. The promoter regions are enriched with various cis-acting elements related to growth and development (8 types), hormone regulation (9 types), and stress responses (6 types). Expression patterns indicate that different CmGATA family members are significantly expressed in seeds, roots, stems, leaves, tendrils, mesocarp, and epicarp, exhibiting distinct tissue-specific expression characteristics. Quantitative fluorescence analysis revealed that five genes, CmGATA3, CmGATA7, CmGATA16, CmGATA22, and CmGATA24, may be highly active under 48-hour drought stress, while CmGATA1 and CmGATA22 may enhance melon resistance to heavy metal lead stress. Additionally, CmGATA22 and CmGATA24 are suggested to regulate melon resistance to Fusarium wilt infection. CmGATA22 appears to comprehensively regulate melon responses to both biotic and abiotic stresses. Lastly, potential protein interaction networks were predicted for the CmGATA family members, identifying CmGATA8 as a potential hub gene and predicting 2230 target genes with enriched GO functions. This study preliminarily explores the expression characteristics of CmGATA genes under drought stress, heavy metal lead stress, and Fusarium wilt infection, providing a theoretical foundation for molecular mechanisms in melon improvement and stress resistance.